Handout Development on Contextual Based-Approach to Improve the Problem Solving Ability of Grade VII Student - Alimatu Saqdiah; Armiati Armiati; Yerizon Yerizon (Fakultas Ilmu Pendidikan UNP)
Problem solving ability is a very important to attainment of objectives mathematics learning. In fact, the problem solving ability of student is still low. One of the efforts to improve the problem solving ability is handout development on contextual based-approach. The purpose of this development research is to know the characteristics handout on contextual based-approach which are valid, practical, and effective. This development research uses a Plomp model consisting of three phases namely : preliminary, prototyping, and assessment. The instruments were used in this study are validation sheets for RPP and handout, questionnaire for teacher and students, sheets of observation, and test. Handout on contextual based-approach has been valid with validity was 3.58 and it was practical with practicality level of the according to the teachers’ response gave 87,86% and students' response was 82.73%. They also efective to improve the problem solving ability of student.